PENGARUH PANDEMI COVID-19 TERHADAP PEMERIKSAAN ANTE NATAL CARE (ANC) IBU HAMIL DI PUSKESMAS CURUG KOTA SERANG TAHUN 2021 - Intan Karlina; Fanny Septiani Farhan (Universitas Duta Bangsa Surakarta, 2022)
During the COVID-19 pandemic, there was a decrease in number of ANC visits, due to various factors includings level of knowledge, anxiety, economic factors, examination fees, and others. This study was to determine the effect of the COVID-19 pandemic on Antenatal Care (ANC) examination visits in pregnant women at the Curug Health Center in Serang City in 2021. An analytical method was conducted with cross sectional approach. Data was collected from questionaire and medical record from 96 respondence. there was a significant relationship between knowledge about COVID-19, knowledge about ANC, age and economic factors related to ANC visits. There was no significant relationship between anxiety and ANC visit at the Curug Health Center in Serang City in 2021